1998
DOI: 10.1080/07448489809595621
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Binge Drinking and Related Problems Among American College Students Between 1993 and 1997 Results of the Harvard School of Public Health College Alcohol Study

Abstract: In 1997, the Harvard School of Public Health College Alcohol Study resurveyed colleges that participated in a 1993 study. The findings revealed little change in binge drinking: a slight decrease in percentage of binge drinkers and slight increases in percentages of abstainers and frequent binge drinkers. Two of 5 students were binge drinkers (42.7%); 1 in 5 (19.0%) was an abstainer, and 1 in 5 was a frequent binge drinker (20.7%). As was true in 1993, 4 of 5 residents of fraternities or sororities were binge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
385
5
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 582 publications
(412 citation statements)
references
References 11 publications
13
385
5
9
Order By: Relevance
“…A high binge school is one of the 30 schools with the highest prevalence of binge drinking among the 116 colleges participating in the 1997 Harvard School of Public Health College Alcohol Study (CAS). Similarly, a low binge school is one of the 30 schools that were lowest in the prevalence of binge drinking (Wechsler et al, 1998). The high binge areas include strata 1 (published numbers) and 2 (unpublished).…”
Section: Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A high binge school is one of the 30 schools with the highest prevalence of binge drinking among the 116 colleges participating in the 1997 Harvard School of Public Health College Alcohol Study (CAS). Similarly, a low binge school is one of the 30 schools that were lowest in the prevalence of binge drinking (Wechsler et al, 1998). The high binge areas include strata 1 (published numbers) and 2 (unpublished).…”
Section: Sampling Designmentioning
confidence: 99%
“…In 1993, the Harvard School of Public Health College Alcohol Study (CAS) found that two in five US college students were binge drinkers (Wechsler, Davenport, Dowdall, Moeykens, & Castillo, 1994) and this rate remained constant in two follow up surveys (1997 and 1999) over a 6-year period (Wechsler, Dowdall, Maenner, Gledhill-Hoyt, & Lee, 1998, 2000a. Among the problems associated with these high levels of alcohol use are what we have termed ''secondhand'' effects.…”
Section: Introductionmentioning
confidence: 99%
“…Binge drinking is especially prevalent among college students. Since three out of five college students are regularly involved in binge drinking, it is the most serious public health problem of American colleges (Wechsler et al, 1998(Wechsler et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Author manuscript; available in PMC 2010 July 7. Castillo, 1994;Wechsler, Dowdall, Maenner, Gledhill-Hoyt, & Lee, 1998;Wechsler & Nelson, 2001).Although other thresholds have been proposed (e.g., 8+ drinks, 12+ drinks; Conigrave, Saunders, & Reznik, 1995;Knupfer, 1984;Nadeau, Guyon, & Bourgault, 1998;White, Kraus, & Swartzwelder, 2006), 5 or more drinks on a single occasion has by far been the standard definition of HED. The origin of this criterion is unclear.…”
mentioning
confidence: 99%